The Mongol Empire. - May, Timothy.
1 online resource (442 pages)
Keywords: This book explores the rise and establishment of the Mongol Empire under Chinggis Khan, as well as its expansion and evolution under his successors. It also examines the successor states (Ilkhanate, Chaghatayid Khanate, the Jochid Ulus (Golden Horde), and the Yuan Empire) from the dissolution of the empire in 1260 to the end of each state.